The high Arctic in extreme winters: vortex, temperature, and MLS and ACE-FTS trace gas evolution - Manney, G. L.; Daffer, W. H.; Strawbridge, K. B.; Walker, K. A.; Boone, C. D.; Bernath, P. F.; Kerzenmacher, T.; Schwartz, M. J.; Strong, K.; Sica, R. J.; Krüger, K.; Pumphrey, H. C.; et al. (HAL CCSD, 2007)
International audience The first three Canadian Arctic Atmospheric Chemistry Experiment (ACE) Validation Campaigns at Eureka (80° N, 86° W) were during two extremes of Arctic winter variability: Stratospheric sudden warmings (SSWs) in 2004 and 2006 were among the strongest, most prolonged on record; 2005 was a record cold winter. New satellite measurements from ACE-Fourier Transform Spectrometer (ACE-FTS), Sounding of the Atmosphere using Broadband Emission Radiometry, and Aura Microwave Limb Sounder (MLS), with meteorological analyses and Eureka lidar and radiosonde temperatures, are used to detail the meteorology in these winters, to demonstrate its influence on transport and chemistry, and to provide a context for interpretation of campaign observations. During the 2004 and 2006 SSWs, the vortex broke down throughout the stratosphere, reformed quickly in the upper stratosphere, and remained weak in the middle and lower stratosphere. The stratopause reformed at very high altitude, above where it could be accurately represented in the meteorological analyses. The 2004 and 2006 Eureka campaigns were during the recovery from the SSWs, with the redeveloping vortex over Eureka. 2005 was the coldest winter on record in the lower stratosphere, but with an early final warming in mid-March. The vortex was over Eureka at the start of the 2005 campaign, but moved away as it broke up. Disparate temperature profile structure and vortex evolution resulted in much lower (higher) temperatures in the upper (lower) stratosphere in 2004 and 2006 than in 2005. Satellite temperatures agree well with Eureka radiosondes, and with lidar data up to 50?60 km. Consistent with a strong, cold upper stratospheric vortex and enhanced radiative cooling after the SSWs, MLS and ACE-FTS trace gas measurements show strongly enhanced descent in the upper stratospheric vortex during the 2004 and 2006 Eureka campaigns compared to that in 2005.